Early Poly Mass Effect (trimethylene-sebasat) On Biodegradation Rate In Liquid Media Using Mucor Miehei In Aerobic - Kholisul Fuad, Akhmad; Mardiana, Diah; Roosdiana, Anna (Natural B, Journal of Health and Environmental Sciences, 2012)
The author has conducted research about the effect of poly(trimethylene-sebacate) mass toward the rate of biodegradation using Mucor miehei in aerobic liquid media. Poly(trimethylene-sebacate) is a biodegradable linear aliphatic polyester, that can be degraded by Mucor miehei lipase. To determine the effect of poly(trimethylene-sebacate) mass in the biodegradation, the mass of poly(trimethylene-sebacate) were varied 0.06 g, 0.08 g, 0.1 g, 0.12 g and 0.14 g. Biodegradation process carried out for 12 hours, using liquid of Complex media, which was nutrient rich for Mucor miehei growth, and solution at pH 5. The resulting CO2 gas was flowed into the 50 mL reservoir of 0.1 M NaOH, followed by titration using 0.05 M HCl and MO (methyl orange) and PP (phenolptalein) indicator. The rate of CO2 gas were 0.287 x 10-3 M/h; 0.102 x 10-3 M/h; 0.137 x 10-3 M/h; 0.016 x 10-3 M/h; and 0.039 x 10-3 M/h respectively. The greater rate of CO2 produced the lower mass of poly(trimethylene-sebacate).